Implementing general practice in Russia: getting beyond the first steps. Issue 7510 (21st July 2005) - Rese, Andrey; Balabanova, Dina; Danishevski, Kirill; McKee, Martin; Sheaff, Rod
Abstract : Russia has been trying to establish a model of primary health care based on integrated general practice. Is it managing to shake off the old attitudes and infrastructures of the Soviet era?